Not only embryo quality but also Endometrial Thickness Contributes to IVF outcome: a retrospective study of all IVF cycles in Yasmin Clinic, Jakarta, Indonesia - Budi Wiweko (Indonesian Socety of Obstetrics and Gynecology, 2010)
Objective: To study the endometrial thickness and embryo quality during In Vitro Fertilization (IVF) cycles in predicting IVF outcome. Methods: This retrospective study involved 206 infertile patients undergoing 218 IVF cycles in Yasmin Clinic, Dr. Cipto Mangunkusumo National Referral Hospital, Jakarta, Indonesia. All IVF cycles were performed from January 2005 until May 2009. The outcome of this study is the clinical pregnancy following IVF cycles. The endometrial thickness was measured on the day of human chorionic gonadotrophin (hCG) administration. The number of embryos that developed ≥ 8 cells on cleavage II represented as the embryo quality. Results: There were 51 among 218 cycles (23.4%) resulted in pregnancy. The endometrial thickness on day of hCG administration was significantly higher in pregnant group compared to non-pregnant group (11.49±1.97 mm versus 10.13±1.93mm; p